Protocols for Proteomic Analysis: Isolation, Solubilization and Hydrolysis by Proteases - Obukhova, E.N.; Khryapova, E.V.; Novikova, S.E.; Kazieva, L.Sh.; Tikhonova, O.V.; Zgoda, V.G. (Biomedical Chemistry: Research and Methods, 2025)
High-throughput studies of protein composition of biological samples have become routine and are used practically in all areas of life sciences. Modern proteomics methods allow reliable identification and quantification of thousands of proteins in a single experiment. The standard procedure for proteomic analysis includes the following steps: 1. isolation and solubilization of proteins, their hydrolysis by proteases; 2. analysis of the resulting peptides by high-performance liquid chromatography with mass spectrometric detection; 3. bioinformatics and statistical processing of the results. This paper presents protocols of the first stage of proteomic analysis, i.e. sample preparation, which are routinely used in the Laboratory of Systems Biology of the Institute of Biomedical Chemistry.